Hygiene and food safety habits in an urban and rural population in isolation by Covid 19 Tacna region, 2020 - Zegarra Mandamiento, Gladys Eliana (2020)
The research aimed to identify changes in hygiene habits and impacts on food security in a rural and urban population in isolation by Covid 19 in the Tacna region. The research was non-experimental and cross-cutting the survey was used as a technique, applying a questionnaire to populations aged 18 to 65, from provinces of Candarave representing the rural area and the province of Tacna classified as urban. Pearson's Chi-square statistic was applied for data analysis. The results show significant and positive changes in hygiene habits in food handling that is more noticeable in urban areas than in rural areas, while negative impacts on food security are more evident in rural areas than in urban areas. It is therefore concluded that there were significant impacts as a result of Covid 19 confinement on hygiene habits and food safety.